Prenatal and early life exposure to traffic pollution and cardiometabolic health in childhood. Issue 1 (4th February 2016) - Fleisch, A. F.; Luttmann‐Gibson, H.; Perng, W.; Rifas‐Shiman, S. L.; Coull, B. A.; Kloog, I.; Koutrakis, P.; Schwartz, J. D.; Zanobetti, A.; Mantzoros, C. S.; Gillman, M. W.; Gold, D. R.; et al.
Summary: Background: Prenatal exposure to traffic pollution has been associated with faster infant weight gain, but implications for cardiometabolic health in later childhood are unknown. Methods: Among 1418 children in Project Viva, a Boston‐area pre‐birth cohort, we assessed anthropometric and biochemical parameters of cardiometabolic health in early (median age 3.3 years) and mid‐ (median age 7.7 years) childhood. We used spatiotemporal models to estimate prenatal and early life residential PM2.5 and black carbon exposure as well as traffic density and roadway proximity. We performed linear regression analyses adjusted for sociodemographics. Results: Children whose mothers lived close to a major roadway at the time of delivery had higher markers of adverse cardiometabolic risk in early and mid‐childhood. For example, total fat mass was 2.1 kg (95%CI: 0.8, 3.5) higher in mid‐childhood for children of mothers who lived <50 m vs. ≥200 m from a major roadway. Black carbon exposure and traffic density were generally not associated with cardiometabolic parameters, and PM2.5 exposure during the year prior was paradoxically associated with improved cardiometabolic profile. Conclusions: Infants whose mothers lived close to a major roadway at the time of delivery may be at later risk for adverse cardiometabolic health.